Wholesale Prices and Industrial Stock Prices During and Immediately After the Two World Wars - Bean, Louis H. (The Review of Economics and Statistics, 1947)
THE course of commodity prices during World War II and the first postwar year has been generally inverse to the course of stock market prices, especially if each is considered in relation to its trend. A similar inverse relationship developed during and after World War I. The commodity price movements of i9i6-20 and I940-46 show roughly the same general pattern, and there is a general similarity between the broad movements of stock prices for the two periods. In each postwar year, i9i8-i9 and I945-46, stock prices advanced sharply, but turned down as commodity prices started rising sharply, and in each case commodity prices remained high several months after the peak in stock prices. These observations are based on the two sets of records in Charts i and 2. Chart i presents the monthly record of wholesale commodity prices from I940 to the fall of I946, and a similar record of industrial stock prices. In order to emphasize the differences in the rate of change in prices, trend lines have been drawn in. They, of course, have no particular significance beyond their aid to